Kooperative Arbeitsplattformen - CSCW-Systeme in Lehr- und Lernkontexten - Schulte, Carsten; Selke, Harald; Huth, Carsten (LOG IN)

Dekonstruktion von Informatiksystemen als Unterrichtsmethode - Zugang zu objektorientierten Sichtweisen im Informatikunterricht - Hampel, Thorsten; Magenheim, Johannes; Schulte, Carsten (INFOS)

Vom Modellieren zum Gestalten - Objektorientierung als Impuls für einen neuen Informatikunterricht? - Schulte, Carsten (Informatica Didactica)

Aufgabenbereiche der Medienbildung im Informatikunterricht - Schulte, Carsten; Scheel, Olaf (INFOS)

Theoriegeleitete Entwicklung und Evaluation von Neuen Medien für die Lehre - Schulte, Carsten (Softwaretechnik-Trends)

Theoriegeleitete Entwicklung und Evaluation von Neuen Medien für die Lehre - Schulte, Carsten (GI Jahrestagung)

Das Sieben-Schritte-Schema zur Dekonstruktion objektorientierter Software - Schulte, Carsten; Block, Ulrich (DDI)

Lehr-Lernprozesse im Informatik-Anfangsunterricht: theoriegeleitete Entwicklung und Evaluation eines Unterrichtskonzepts zur Objektorientierung in der Sekundarstufe II - Schulte, Carsten

Thinking in Objects and their Collaboration: Introducing Object-Oriented Technology - Schulte, Carsten; Magenheim, Johannes; Niere, Jörg; Schäfer, Wilhelm (Computer Science Education)

Novices' expectations and prior knowledge of software development: results of a study with high school students - Schulte, Carsten; Magenheim, Johannes (ICER)

Beiträge der Objektorientierung zu einem Kompetenzmodell des informatischen Modellierens - Brinda, Torsten; Schulte, Carsten (INFOS)

Erwartungen und Wahlverhalten von Schülerinnen und Schülern gegenüber dem Schulfach Informatik - Ergebnisse einer Umfrage - Schulte, Carsten; Magenheim, Johannes (INFOS)

Social, ethical and technical issues in informatics - An integrated approach - Magenheim, Johannes; Schulte, Carsten (EAIT)

Research perspectives on the objects-early debate - Lister, Raymond; Berglund, Anders; Clear, Tony; Bergin, Joe; Garvin-Doxas, Kathy; Hanks, Brian; E. Hitchner, Lewis; Luxton-Reilly, Andrew; Sanders, Kate; Schulte, Carsten; L. Whalley, Jacqueline (SIGCSE Bulletin)

What do teachers teach in introductory programming? - Schulte, Carsten; Bennedsen, Jens (ICER)

A Competence Model for Object-Interaction in Introductory Programming - Bennedsen, Jens; Schulte, Carsten (PPIG)

Gestaltung von Informatikseminaren unter Einsatz von Videokonferenzen - Schulte, Carsten; Thomas, Marco (HDI)

3. Workshop der GI-Fachgruppe "Didaktik der Informatik", 19.-20. Juni 2006 an der Universität Potsdam

Attitudes towards computer science-computing experiences as a starting point and barrier to computer science - Schulte, Carsten; Knobelsdorf, Maria (ICER)

Lesen im Informatikunterricht - Schulte, Carsten (INFOS)

Das informatische Weltbild von Studierenden - Schulte, Carsten; Knobelsdorf, Maria (INFOS)

Block Model: an educational model of program comprehension as a tool for a scholarly approach to teaching - Schulte, Carsten (ICER)

Duality Reconstruction - Teaching Digital Artifacts from a Socio-technical Perspective - Schulte, Carsten (ISSEP)

What are information technology's key qualifications? - Dörge, Christina; Schulte, Carsten (ITiCSE)

Digitale Artefakte und Schlüsselkompetenzen im Informatikunterricht der Sekundarstufe I - Schulte, Carsten; Dörge, Christina (DDI)

An evaluation of object oriented example programs in introductory programming textbooks - Börstler, Jürgen; S. Hall, Mark; Nordström, Marie; H. Paterson, James; Sanders, Kate; Schulte, Carsten; Thomas, Lynda (SIGCSE Bulletin)

Qualitätssicherung in einer interaktiven und lerneraktivierenden E-Learning-Umgebung - Schulte, Carsten; Tolksdorf, Robert (DeLFI Workshops)

Empirical comparison of objects-first and objects-later - Ehlert, Albrecht; Schulte, Carsten (ICER)

Bridging ICT and CS: educational standards for computer science in lower secondary education - Brinda, Torsten; Puhlmann, Hermann; Schulte, Carsten (ITiCSE)

Unterschiede im Lernerfolg von Schülerinnen und Sch\üern in Abhängigkeit von der zeitlichen Reihenfolge der Themen (OOP-First bzw. OOP-Later) - Ehlert, Albrecht; Schulte, Carsten (INFOS)

Informatik im Kontext (IniK) - Ein integratives Unterrichtskonzept für den Informatikunterricht - Koubek, Jochen; Schulte, Carsten; Schulze, Peter; Witten, Helmut (INFOS)

Dualitätsrekonstruktion als Hilfsmittel zur Entwicklung und Planung von Informatikunterricht - Schulte, Carsten (INFOS)

BlueJ Visual Debugger for Learning the Execution of Object-Oriented Programs? - Bennedsen, Jens; Schulte, Carsten (TOCE)

Comparison of OOP first and OOP later: first results regarding the role of comfort level - Ehlert, Albrecht; Schulte, Carsten (ITiCSE)

10th Koli Calling International Conference on Computing Education Research, Koli Calling '10, Koli, Finland, October 28-31, 2010

Didaktik der Informatik - Möglichkeiten empirischer Forschungsmethoden und Perspektiven der Fachdidaktik. 6. Workshop der GI-Fachgruppe "Didaktik der Informatik", 16. - 17. September 2010 in Oldenburg

Analysis of code reading to gain more insight in program comprehension - Busjahn, Teresa; Schulte, Carsten; Busjahn, Andreas (Koli Calling)

ProspectiveTeachers@Research: CS teacher education revised - Hornung, Malte; Schulte, Carsten (Koli Calling)

Informatik begreifen - Zur Nutzung von Veranschaulichungen im Informatikunterricht - Kalbitz, Manuela; Voss, Hendrik; Schulte, Carsten (INFOS)

Das Schülerlabor als Ort der Informatiklehrerbildung - Schulte, Carsten (INFOS)

The technical potential of digital boards - Selke, Harald; Winkelnkemper, Felix
This article explains the technical potential of digital boards with which more and more schools are being equipped. A consideration of current usage scenarios of these interactive whiteboards shows that a large part of this potential is still unused and the deficits of the software often have to be circumvented with tricks, especially for use in demanding, student-oriented lessons. Finally, the further development of existing teaching scenarios using this technical potential shows that considering the technical possibilities of digital boards can motivate new didactic scenarios.

E-learning strategies: best practice or careful structural renewal? - Keil, Reinhard; Schild, Christian; Winkelnkemper, Felix

Koli Calling 2009 and 2010 - Schulte, Carsten; Suhonen, Jarkko (Computer Science Education)

Computer science at school/CS teacher education: Koli working-group report on CS at school - Schulte, Carsten; Hornung, Malte; Sentance, Sue; Dagiene, Valentina; Jevsikova, Tatjana; Thota, Neena; Eckerdal, Anna; Peters, Anne-Kathrin (Koli Calling)

Uncovering structure behind function: the experiment as teaching method in computer science education - Schulte, Carsten (WiPSCE)

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

The use of code reading in teaching programming - Busjahn, Teresa; Schulte, Carsten (Koli Calling)

Object Interaction Competence Model v. 2.0 - Bennedsen, Jens; Schulte, Carsten (LaTiCE)

PCK and reflection in computer science teacher education - Buchholz, Malte; Saeli, Mara; Schulte, Carsten (WiPSCE)